A test of usefulness of a commercially available mill "waste product" (AB-84) as feed for starving reindeer - Mathiesen, Svein D.; Rognmo, Arne; Blix, Arnoldus Schytte (Rangifer, 1984)
Three Norwegian reindeer were first fed lichen ad libitum for 40 days, then they were starved for 3 days, and thereafter offered a commercially available mill «waste product» (AB-84) ad libitum. One animal refused to eat AB-84 and was excluded. When eating lichen average daily dry matter intake was 1.1 ± 0.4 kg, while when eating AB-84 after the starvation period it averaged 1.1 kg at day 1, increasing to 2.5 kg at day 7. After 12 days daily dry matter intake varied between 2 and 4 kg. The rumen dry matter percentage was 16 when eating lichen, 6 after 2 days of starvation, and 17 after eating AB-84 for 5 days. Ruminal pH was 6.4 ± 0.3 when eating lichen, increasing to 7.4 after 3 days of starvation and dropping to an all time low of 6.1, 12 hours after refeeding. The viable bacterial count was 4.7 x 1010 ± 2.7, 5.5 x 108 ± 2.0 and 3.1 x 1010 ± 1.7/ml rumen fluid when the animals were eating lichen, had starved for 3 days and had been eating AB-84 for 5 days, respectively. The rumen ciliate protozoa numbered 17.1 x 105 ± 2.7/ml rumen fluid, when eating lichen, dropping to 4.3 x 105 ± 0.6./ml after 3 days of starvation. A further drop to 1.8 x 10s ± 0.5/ml was observed 1 day after refeeding, but the rumen ciliate number was normalized at 15 x 105 ± 1/ml already 8 days after refeeding. These results indicate that the mill «waste product» (AB-84) is very well tolerated even by reindeer suffering from starvation. Since it is moreover commercially available at a favourable price it could be of interest to reindeer herders. In any case, it deserves to be tested under controlled conditions on a larger number of animals. En test på anvendeligheten av kornavrens (AB-84) som for til utsultet rein. Abstract in Norwegian / Sammendrag: Tre norske rein ble gitt lav ad libitum i 40 dager, sultet i 3 dager og deretter gitt kornavrens (AB-84) ad libitum. Ett av dyrene nektet å spise AB-84 og ble satt ut av forsøket. Daglig foropptak i kg tørrstoff var gjennomsnittlig 1.1 ± 0.4 kg under lavforing, mens opptaket av AB-84 var gjennomsnittlig 1.1 kg/dag den første dagen etter sulteperioden. Den syvende dagen var opptaket 2.5 kg/dag, og varierte mellom 2 og 4 kg/dag etter 12 dager. Prosent tørrstoff i vominnholdet var 16 under lavforing, 6 etter 2 dagers sult og 17 etter 5 dagers foring med AB-84. pH i vominnholdet ble målt til gjennomsnittlig 6.4 ± 0.3 under lavforing, 7.4 etter 3 dagers sult og falt bare til 6.1, som lavest målte verdi, etter 12 timers ad lib. tilgang på AB-84. Antall levende bakterier pr. ml vomsaft var henholdsvis 4.7 x 1010 ± 2.7, 5.5 x 10" ± 2.0 og 3.1 x 1010 ± 1.7 når dyrene spiste lav, hadde sultet i tre dager og hadde spist AB-84 ad lib. i fem dager. Antall eiliater var 17.1 x 105 ± 2.7 pr. ml vomsaft når dyrene spiste lav og 4.3 x IO5 ± 0.6 etter tre dagers sult. Etter en dags ad lib. tilgang på AB-84 var antallet 1.8 x 105 ± 0.5 pr. ml og etter fem dager 7.7 x 105 ± 1.8/ml. Disse resultatene indikerer at selv sultet rein tolererer kornavrens (AB-84) meget godt, og da foret er kommersielt tilgjengelig til en rimelig pris, kan det være av interesse for reindriftsutøvere. I alle tilfeller fortjener foret å bli utprøvet på et større antall dyr under kontrollerte betingelser. Koe viljaperkeen (AB-84) käyttökelpoisuudesta rehuna nälkiintyneelle porolle. Abstract in Finnish / Yhteenveto: Kolmea norjalaista poroa ruokittiin jäkälällä ad libitum 40 päivää, annettiin nähdä nälkää 3 päivää ja sen jälkeen ruokittiin taas viljaperkeellä (AB-84) ad libitum. Yksi eläimistä kieltäytyi syömästä AB-84 ja näin ollen jouduttiin poistamaan kokeilusta. Päivittäinen rehuntarve kuiva-ainekilossa oli keskimäärin 1.1 ± 0,4 kg jäkäläruokinnassa, kun taas AB-84 ruokinta oli keskimäärin 1.1 kg/päivässä ensimmäisenä päivänä nälkäkauden jälkeen. Seitsemäntenä rehunkulunki oli 2.5 kg päivässä, vaihdellen 2-4 kg päivässä 12 päivän jälkeen. Kuiva-ainesprosentti pötsinsisällössä oli 16 jäkäläruokinnassa, 6 kahden päivän nälän jälkeen ja 17 viisipäiväisen AB-84 ruokinnan jälkeen. Pötsinsisällön happamuus, pH mitattiin keskimäärin 6.4 ± 0.3 jäkäläruokinnassa, 7.4 kolmipäiväisen nälän jälkeen ja väheni vain 6.1:een, joka on alhaisin mitattu arvo, 12 tunnin AB-84 ruokinnan ad lib. jälkeen. Elävien bakteerien lukumäärä pötsinestemillilitraa kohti oli kyseelliset 4.7 x 1010 ± 2.7, 5.5 x 10" ± 2.0, ja 3.1 x 1010 ± 1.7 kun eläimet söivät jäkälää, olivat nälkiintyneet 3 päivää ja syöneet AB-84 ad üb. viisi päivää. Ciliatmäärä oli 17.1 x 105 ± 2.7 pötsinestemillilitraa kohti eläinten syötyä jäkälää ja 4.3 x 105 ± 0.6 kolmipäiväisen nälkiintymisen jälkeen. Yhden päivän AB-84 ruokinnan ad lib. jälkeen määrä oli 1.8 x 105 ± 0.5 millilitralta ja viiden päivän jälkeen 7.7 x 105 ± 1.8 millilitralta. Nämä tulokset osoittavat, että jopa nälkiintynyt poro sietää viljaperkettä (AB-84) erittäin hyvin, ja koska rehua on saatavana kohtuulliseen hintaan se voinee kiinnostaa poromiehiä. Joka tapauksessa rehua kannattaa kokeilla tarkkailtuin edellytyksin suuremmalle eläinryhmälle.